PENINGKATAN PENILAIAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM DENGAN MENERAPKAN MODEL KOOPERATIF TIPE MAKE A MACTH PADA SISWA KELAS VIII SMPN 3 BATI-BATI KECAMATANBATI-BATI KABUPATEN TANAH LAUT - Risna Dewi Arfianti; Muhamad Ramli (ADDABANA: Jurnal Pendidikan Agama Islam, 2019)
The purpose of this research is to find out the assessment of the results of the study of Islamic religious education by applying a cooperative model of Make a Match type in students of Grade VIII SMPN 3 Bati-Bati subdistrict of Bati-Bati of Tanah Laut Regency and to know the implementation of a cooperative learning model of Make a MACTH in Islamic religious education. This research is qualitative descriptive research with a type of action class research participant. The subject in this study was all students of grade VIII SMPN 3 Bati-Bati. While the object in this study is improved assessment of learning outcomes and the process of implementing cooperative learning model type Make a Match. Based on the results of the research, it is noted that through the implementation of the type of cooperative learning model of Make a Match can improve the assessment of learning outcomes of Islamic education in grade VIII students SMPN 3 Bati-Bati. This can be known from the successful research indicators that are qualitative indicators and quantitative indicators. The process of applying a cooperative learning model of the Make a Match type in Islamic religious education in grade VIII students SMPN 3 Bati-Bati runs effectively and efficiently according to the steps specified. This is evident from the increasing active students in following the learning process of Islamic religious education. Keywords: enhancement, learning outcomes, Islamic education, learning Model, Make a Match.